Standard specification for Cold-Drawn Buttweld Carbon Steel Mechanical Tubing (American Society of Testing Materials, 2006)
This specification covers cold-drawn buttweld carbon steel tubes for use as mechanical tubing. This specification covers round, square, rectangular, and special shape mechanical tubing.